Rebuilding Public Institutions Together : Professionals and Citizens in a Participatory Democracy. - Dzur, Albert W. (Ithaca : Cornell University Press, 2017)
No detailed description available for "Rebuilding Public Institutions Together".
REBUILDING PUBLIC INSTITUTIONS TOGETHER -- Contents -- Introduction -- I: This Problem Belongs to Everyone -- II: What Is a Democratic Professional? -- III: Why Are Public Institutions Repellent to Citizen Agency? -- IV: Thinking (and Acting) for Ourselves: Rebuilding Public Institutions -- V: Growing Cultures of Participatory Innovation -- Conclusion: Democratic Professionals on Campus? -- Acknowledgments -- Notes -- About the Author.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Social advocacy--United States; Electronic books